Constructing Pax Nigeriana? The Media and Conflict in Nigeria-Equatorial Guinea Relations (Nordic Journal of African Studies, 2001)
The paper discusses the reasons for tension between Nigeria and Equatorial Guinea over the past decades. Although the presence of the Nigerian labour force in Equatorial Guinea has been considered the principal source of tension, the paper argues that power politics should not be excluded. The relatively weak position of Equatorial Guinea as a neighbour of populous and wealthy Nigeria might have significant contribution to the foreign policy practised by the former. The analysis of the Nigerian media, especially the writings in the Nigerian newspapers and magazines, shows its dual role of mirroring, and at the same time influencing, a particular reality. (Ed.)